2022
DOI: 10.1002/job.2634
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down and bottom‐up: Examining reciprocal relationships between leader humility and team helping behavior

Abstract: Based on social exchange theory, we develop and test a longitudinal model in which leaders' expressed humility and team members' helping behavior reciprocally influence each other over time and ultimately predict subsequent team performance and turnover. Using multisource, 3-wave repeated measures data from 281 work teams, our cross-lagged panel modeling results supported the hypotheses. We found that leader humility increased subsequent team helping behavior, and team helping behavior also promoted leader hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Following social exchange theory, prior research suggests that leaders who express humility develop positive interpersonal interactions with their followers, then fostering positive reactions (Carnevale et al, 2019;Kelemen et al, 2022;Nguyen et al, 2020;Wang et al, 2022). For example, Cho et al (2021) found that employees positively influenced by leader humility feel trusted and then increased OCB toward coworkers and the organization.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Following social exchange theory, prior research suggests that leaders who express humility develop positive interpersonal interactions with their followers, then fostering positive reactions (Carnevale et al, 2019;Kelemen et al, 2022;Nguyen et al, 2020;Wang et al, 2022). For example, Cho et al (2021) found that employees positively influenced by leader humility feel trusted and then increased OCB toward coworkers and the organization.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…This issue is particularly important to non-core workers who have less career experience and are reliant upon their more senior coworkers for resources to become successful in their careers. Scholars have used social exchange theory to support some of their empirical evidence that employees are encouraged to meet organizational obligations and expectations without relying on contractual governance mechanisms (Wang et al ., 2022). This is particularly true among employees who have accumulated a wealth of career experiences.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In general, humble leaders are self-effacing and positive and caring toward others (Vera and Rodriguez-Lopez, 2004). The positive outcomes of HL have been explored in previous research (Bharanitharan et al , 2021) such as its impact on ethical behavior (Naseer et al , 2020), work engagement (Ma et al , 2019; Li et al , 2021), psychological safety (Qian et al , 2020), creativity (Lei et al , 2021), knowledge sharing intention (Nguyen et al , 2020), followers’ constructive voice (Bharanitharan et al , 2019), relational energy (Wang et al , 2018a, 2018b), team helping behavior (Wang et al , 2022), organizational citizenship behavior (Qin et al , 2021), employee performance (Bin et al , 2021) and organizational performance (Petrenko et al , 2019).…”
Section: Introductionmentioning
confidence: 99%